Retrograde axonal transport of herpes simplex virus: Evidence for a single mechanism and a role for tegument - Bearer, E. L. (The National Academy of Sciences, 2000)
Herpes simplex virus type I (HSV) typically enters peripheral nerve terminals and then travels back along the nerve to reach the neuronal cell body, where it replicates or enters latency. To monitor axoplasmic transport of HSV, we used the giant axon of the squid, Loligo pealei, a well known system for the study of axoplasmic transport. To deliver HSV into the axoplasm, viral particles stripped of their envelopes by detergent were injected into the giant axon, thereby bypassing the infective process. Labeling the viral tegument protein, VP16, with green fluorescent protein allowed viral particles moving inside the axon to be imaged by confocal microscopy. Viral particles moved 2.2 ± 0.26 μm/sec in the retrograde direction, a rate comparable to that of the transport of endogenous organelles and of virus in mammalian neurons in culture. Electron microscopy confirmed that 96% of motile (stripped) viral particles had lost their envelope but retained tegument, and Western blot analysis revealed that these particles had retained protein from capsid but not envelope. We conclude that (i) HSV recruits the squid retrograde transport machinery; (ii) viral tegument and capsid but not envelope are sufficient for this recruitment; and (iii) the giant axon of the squid provides a unique system to dissect the viral components required for transport and to identify the cellular transport mechanisms they recruit.